COMPARATIVE STUDY OF URETEROSCOPY VERSUS EXTRACORPOREAL SHOCK WAVE LITHOTRIPSY IN MANAGEMENT OF UPPER URETERIC CALCULI - Purnima Pathak, SP Tripathi*, DK Jain, Dhinesh Kumar M, (Innovative Journal of Medical and Health Sciences, 2018)
AIMS AND OBJECTIVE: To compare and assess the safety and efficacy of Ureteroscopy (URS) versus Extracorporeal shock wave lithotripsy (ESWL) in the management of upper ureteric calculi and look for any complications which are specific to ESWL or Ureteroscopy. METHODOLOGY: All patients presenting to the hospital with symptoms of ureteric colic/calculi were evaluated. Of them, a total of sixty successive patients that on evaluation had upper ureteric stones of 5-15 mm were included in this study. Out of 60 patients 30 was treated with ESWL and 30 underwent Ureteroscopy. The safety, efficacy and complications were compared between groups immediately and at three months after the procedure. Data were analysed using Fischer exact test in SPS version 19. RESULT: The immediate percentage of clearance and clearance at three months follow up for URS and ESWL group was analysed using t-test and it was found that there exists a significant difference in the immediate clearance rate (p value=0.030), however there was no significant difference in three months follow up for stone clearance in both the groups (p=0.999). The difference in the number of complication to both group was analysed using Fisher’s exact test and it was found that complication rates were significantly higher in the URS group compared to the ESWL group(p=0.004). CONCLUSION: ESWL is the preferred choice of treatment for proximal ureteric stones, in our study results suggest that Ureteroscopy is a viable and safe alternative, with an advantage of obtaining an immediate stone-free status.